Thermodynamics, Charge Transfer and Practical Considerations of Solid Boosters in Redox Flow Batteries - Moghaddam Mahdi; Sepp Silver; Wiberg Cedrik; Bertei Antonio; Rucci Alexis; Peljo Pekka (MDPI, 2022)
Solid boosters are an emerging concept for improving the performance and especially the energy storage density of the redox flow batteries, but thermodynamical and practical considerations of these systems are missing, scarce or scattered in the literature. In this paper we will formulate how these systems work from the point of view of thermodynamics. We describe possible pathways for charge transfer, estimate the overpotentials required for these reactions in realistic conditions, and illustrate the range of energy storage densities achievable considering different redox electrolyte concentrations, solid volume fractions and solid charge storage densities. Approximately 80% of charge storage capacity of the solid can be accessed if redox electrolyte and redox solid have matching redox potentials. 100 times higher active areas are required from the solid boosters in the tank to reach overpotentials of <10 mV.